Técnica de Flossing como tratamiento fisioterapéutico para la corrección de la inestabilidad de tobillo - De La Cruz De La Cruz, Mishel Patricia (2022)
ABSTRACT The investigative work was obtained through a search of bibliographic data on the Flossing technique as a physiotherapeutic treatment for the correction of ankle instability, through an updated compilation of high-impact scientific databases.For the development of the project, the bibliographic search consisted of the collection of 60 scientific articles, all of which were analyzed applying the inclusion and exclusion criteria, subsequently qualified by means of the Physiotherapy Evidence Database (PEDro) methodological assessment scale. with a score higher than 5, the result was 30 scientific articles in English and translated into Spanish.The scientific databases used were: PubMed, Elseiver, Researchgate, Pubmed Central, Cerdarville University, Journals of Medical Biomedical and Applied Sciences, Journal of Physical Therapy, International Journal of Human Movement and Sports Sciences, Dialnet. With articles in the line of time from 2016 to 2022 in all 30 items.In the results obtained from the research, the clinical trials carried out by several authors show that the Flossing technique applied as a treatment for ankle instability has positive effects where it provides increased joint range, improves ankle mechanics, provides injuries and reduces symptoms. of pathology. Keywords: Flossing, ankle instability, joint range, ankle mechanics.